Transenamel and transdentinal penetration of H2O2 in restored bovine teeth - Briso, André Luiz Fraga [UNESP]; Gonçalves, Rafael Simões; de Azevedo, Fernanda Almeida [UNESP]; Gallinari, Marjorie de Oliveira [UNESP]; Santos, Paulo Henrique dos [UNESP]; Fagundes, Ticiane Cestari [UNESP] (My University, 2015)
Purpose: To quantify hydrogen peroxide (H2O2) penetration into restored bovine teeth subjected to whitening treatment. Materials and Methods: Seventy-five enamel/dentin disks were divided into 5 groups (n = 15): intact disks (G1); cavity preparation only (G2); conventional adhesive system and composite resin (G3); resin-modified glass-ionomer cement (G4); and self-etching adhesive only (G5). After 24 h, the disks were placed into artificial pulp chambers containing an acetate buffer solution, and the first whitening session was performed using a 35% H2O2 (hydrogen peroxide) product. The disks were submitted to 10,000 thermal cycles and then stored for 1 year in deionized water. After this period, a second whitening session was performed. After each whitening procedure, the buffer solutions were analyzed for optical density in a spectrophotometer to assess the amount of H2O2 that had diffused. ANOVA and Tukey's test were used to compare the different groups and a Student's t-test was used to compare the different times (p ≤ 0.05). Results: Prior to aging, group 2 had the highest penetration of H2O2; the other groups showed similar, lower penetration. After thermocycling and aging, all groups showed a significant increase in H2O2 penetration. The greatest penetration of H2O2 into the pulp chamber was found in groups 2 and 5. Conclusion: Aged restorations allowed greater H2O2 permeation through the tooth structure.
Keywords: Adhesive; Dental bleaching; Hydrogen peroxide; Restoration